In mathematics, a system of linear equations consists of two or more linear equations with two or more unknown variables. Solving a system of linear equations involves determining the values of the unknown variables that meet the conditions set by all the equations at the same time. Various methods can be employed to find these solutions, including the graphical method, substitution method, elimination method, cross-multiplication method, and more. In this article, we will focus on the Elimination Method, providing a detailed explanation and step-by-step guide to solving systems of linear equations using this technique, along with illustrative examples.
The Elimination Method is an algebraic approach for solving systems of linear equations. In this method, you add or subtract the equations to eliminate one of the variables, leading to an equation with only one variable. If the coefficients of one variable are the same but have opposite signs, you can add the equations to eliminate that variable.
If the equations are not initially set up to directly add or subtract to eliminate a variable, you can start by multiplying one or both equations by a constant to create an equivalent system where elimination is possible. Once the coefficients of one variable are the same (either with opposite signs for addition or the same signs for subtraction), you can then subtract or add the equations to eliminate that variable.
The Elimination Method formula typically involves the following steps:
Let's understand this process with a general example.
General Case: Consider the system of two linear equations:
ax + by = c (1)
px + qy = r (2)
To use the elimination method, follow these steps:
apx + bpy = cp (3)
apx + aqy = ar (4)
Now, the coefficients of x in equations (3) and (4) are the same.
(a p x+b p y)-(a p x+a q y)=c p-a r
Simplifying, we get:
b p y-a q y=c p-a r
(b p-a q) y=c p-a r
a x+b y=c
Solving for x:
a x=c-b y
Putting the value of y
By following these steps, you can find the values of x and y in the given system of linear equations.
Solving a system of three equations using the Elimination Method involves extending the technique used for two equations. Here's a step-by-step outline:
Example 1: Consider the system of equations:
Solution: Step 1: Adjust Coefficients
To eliminate y, we need the coefficients of y to be equal (with opposite signs). We can achieve this by multiplying the first equation by 3 and the second equation by 2:
This results in:
Step 2: Eliminate One Variable
Now, add the two equations to eliminate y:
(9 x+12 y)+(10 x-12 y)=30-4
Simplifying, we get:
Step 3: Solve for the Remaining Variable
Substitute back into the first equation:
Simplifying:
Solution:
The solution to the system is:
Example 2: Consider the system of equations:
Solution: Step 1: Adjust Coefficients
To eliminate y, we can multiply the second equation by 3:
Step 2: Eliminate One Variable
Add the two equations to eliminate y:
(2x + 3y) + (12x – 3y) = 8 + 6
Simplifying, we get:
Step 3: Solve for the Remaining Variable
Substitute x = 1 back into the first equation:
Solution:
The solution to the system is:
(1, 2)
Example 3: Solve 3x + 4y = 10 and 2x– 2y = 2
Solution: 3x + 4y = 10 …… (1)
Let us eliminate y so multiple equation (1) by 1 and equation (2) by 2 and then add
Putting the value of x = 2 in equation (1)
3x + 4y = 10
⇒ 3(2) + 4y = 10
⇒ 6 + 4y = 10
⇒ 4y = 10 – 6 = 4
So, x = 2, y = 1
Example 5: Solve 3x – 5y –4 = 0 and 9x = 2y + 7
Solution:
3x –5y – 4 = 0 ⇒ 3x – 5y = 4 …………. (1)
9x = 2y + 7 ⇒ 9x – 2y = 7 …………. (2)
Let us eliminate x. So, multiply equation 1 by 3 and equation 2 by 1 and then subtract
(3x–5y = 4) ×3
(9x–2y = 7) × 1
Putting value of y in (1)
3x – 5y = 4
So
Example 6: Solve
⇒ 3x +4y = –6 …..(1)
⇒ 3x –y = 9 = …..(2)
Let's eliminate x. Subtract equation (2) from equation (1)
y=-3
Putting value in eq (1)
3x + 4 (–3) = –6 ⇒ 3x – 12 = – 6
⇒ 3x = – 6 + 12 ⇒ 3x =
So, x = 2 and y = –3
Example 7: Solve x + 2y –z = 2, 2x – 3y +z = –1 and 5x–y –2z = –3
Solution :
x + 2y – z = 2 ..... (1)
2x –3y + z = –1 ..... (2)
5x–y – 2z= –3 ..... (3)
Let us first eliminate z, so Add equation (1) and equation (2)
3x – y = 1 … (4)
Now we will eliminate z from equation (2) and equation (3). So Multiply equation (2) by 2 and add equation (3)
(2x–3y + z = –1)×2 ⇒
(5x–y–2z = –3) ×1 ⇒
9x – 7y = – 5 … (5)
Now, solve equation (4) and equation (5) by elimination method
So let us eliminate x so multiply equation 4 and subject
(3x – y = 1) × 3
(9x–7y = –5) ×1
\begin{aligned}
& 9 x-3 y=3 \\
& 9 x-7 y=-5 \\
& -\quad+\quad+ \\
& \hline 4 y=8
\end{aligned}
y=\frac{8}{4}
Putting value of y in equation 4
3x – (2) = 1 ⇒ 3x –2 = 1 ⇒ 3x = 3
Putting the value of x and y in equation (1)
x + 2 y – z = 2
⇒ (1) + 2(2) – z = 2
⇒ 1 + 4 – z = 2
⇒ –z = 2 –5
⇒ –z = –3
So, x = 1, y = 2 and z = 3 are the solution of linear equation with 3 variables.
(Session 2025 - 26)